Building the blocks for open science - Sule, Sam (Septentrio Conference Series, 2022)
The value and importance of open science is a central component of how we move research and knowledge forward – sharing all elements of research is fundamental to trust, integrity and reproducibility and therefore the advancement of discovery and trusted knowledge.As a community, however, we need to get better at taking concrete steps to drive forward appropriate measures. Encouraging open sharing and research practices, promoting their benefits, and building an evidence based approach to their value – whilst important, are on their own, not enough. Collaboration across all stakeholders needs to take place – policy makers, funders, publishers, librarians, researchers and organisations/institutions. These are all important conversations that need to continue to take place to effect positive change through collaboration, awareness and innovation. Coupling real world examples with clear policy, better credit and reward systems, better tools and services, explicit funding, practical help and answers to common questions are all essential factors in accelerating openness and sharing to an established norm.There are no easy answers, and no “silver bullet”, but there is much we can act on now.This poster will draw on the thoughts of those key stakeholders across our sector to talk through the building blocks to true sustainable open science – from a code and data, platform, librarian, researcher and publisher perspective – whilst we may all be a small part of the cog, by each playing our part we can contribute, more than we have been able to before, in building the blocks for open science.
Keywords: open science; research integrity; publishing; collaboration